EVIDENCE FOR THE PRESENCE OF SUBMICRON SULFURIC ACID PARTICLES IN SUMMER ANTARCTIC ATMOSPHERE : PRELIMINARY RESULTS - ヤマト, マサヒコ; イワサカ, ヤスノブ; オカダ, キクオ; オノ, アキラ; ニシオ, フミヒコ; フカボリ, マサシ; YAMATO, Masahiko; IWASAKA, Yasunobu; OKADA, Kikuo; ONO, Akira; NISHIO, Fumihiko; FUKABORI, Masashi (National Institute of Polar Research, 1987)
P(論文) Direct samplings of aerosol particles in the summer Antarctic atmosphere were carried out at Syowa Station (69°00′S, 39°35′E) and Asuka Camp (71°31′S, 24°07′E) in 1985 and 1986. To determine the molecular state of submicron sulfate particles, a vapor-deposited calcium thin film method was used. It was proved directly that sulfuric acid particles predominantly existed at Syowa Station and Asuka Camp in the summer Antarctic atmosphere. departmental bulletin paper